The role of the baselines in the law of the sea and the maritime delimitation process between Peru and Chile - Maúrtua de Romaña, Óscar (2020)
This article develops the role of the baselines for the delimitation of the maritime spaces of the States, according to the UNCLOS, as well as its importance for Peru and for the demand of its legitimate claims before the International Court of Justice in the maritime dispute with Chile.